Acceptance of the use of silver fluoride among Brazilian parents of children with special health care needs - Potgieter, N.; Pereira, V.; Elias, R.; Charone, S.; Groisman, S. (Frontiers in Oral Health, 2024)
Background Children with special health care needs including Down Syndrome, Autism Spectrum Disorder and Down Syndrome experience difficulties in receiving dental treatment. Silver Diamine Fluoride (SDF) and Silver Fluoride (SF) are a minimally invasive treatments options to arrest dental caries without sedation; local or general anaesthesia (GA). Aim Evaluation of Brazilian's parents' acceptance of the use of SF in CSHCN. Methods After receiving education on SF, 100 Parents of CSHCN completed a questionnaire concerning their acceptance of SF, in different dental situation. Result Majority of parents (74,5%) agreed to the use of SF for their children. SF was more acceptable on posterior teeth (74,5%) when compared to its use on anterior teeth (43,1%). Parents accepted to use SF in order: to reduce infection and pain (82,4%); to avoid dental injection (72,5%) and treatment under GA (84,3%). The Majority of parents accepted the properties of SF (82,4%) and Silver (80,4%). Conclusion Silver Fluoride was accepted as a treatment option for caries, by Brazilian parents of CSHCN. SF should be considered as a treatment option for caries limited to dentine for CSHCN, taking into consideration the individual needs and opinions with regard to aesthetics and exposure to fluoride and silver.